DEWAN PERWAKILAN RAKYAT REPUBLIK INDONESIA: STUDI PERILAKU ANGGOTA DALAM MELAKSANAKAN KEKUASAAN - Asran Jalal (Jurnal Ilmu dan Budaya, 2020)
This article discusses the behavior of Members of the Republic of Indonesia's Representative Council (DPR RI) in the 2014-2019 period in exercising their powers. DPR members for the 2014-201 period were 17 sentenced to imprisonment by the Corruption Court (Corruption), and involved Provincial Government Officials, Local Government Officials and Entrepreneurs. The question is how is the relationship model of DPR RI members, Local Government Officials, and Entrepreneurs doing corruption? What environment supports the ongoing corruption of DPR members. Forms of corruption DPR members receive money from Local Government Officers of Maluku Province, North Maluku Province, and Local Government Officials of Deiyai Regency, Papua Province. The Model of Relationship between Members of the DPR and Local Government Officials, and the relations between Regional Officials and Entrepreneurs are mutually beneficial. Members of the House of Representatives receive money for their services to fight for regional government development projects. Local Government officials are willing to give money to DPR members, approval of the proposed development project is approved by the DPR according to his proposal. Local Government Official money comes from Entrepreneurs who will carry out regional development projects.The environment that supports the corrupt behavior of DPR members comes from the environment of DPR members who mutually support and cooperate in obtaining money, the process of becoming a DPR member who needs a lot of money, hidden support from party elites, the interests of Provincial Government Officials to obtain development budgets according to their proposals, support indirectly from the entrepreneur.